Terrestrial support of aquatic food webs depends on light inputs: a geographically‐replicated test using tank bromeliads. Issue 8 (August 2016) - Farjalla, Vinicius F.; González, Angélica L.; Céréghino, Régis; Dézerald, Olivier; Marino, Nicholas A. C.; Piccoli, Gustavo C. O.; Richardson, Barbara A.; Richardson, Michael J.; Romero, Gustavo Q.; Srivastava, Diane S.
Abstract: Food webs of freshwater ecosystems can be subsidized by allochthonous resources. However, it is still unknown which environmental factors regulate the relative consumption of allochthonous resources in relation to autochthonous resources. Here, we evaluated the importance of allochthonous resources (litterfall) for the aquatic food webs in Neotropical tank bromeliads, a naturally replicated aquatic microcosm. Aquatic invertebrates were sampled in more than 100 bromeliads within either open or shaded habitats and within five geographically distinct sites located in four different countries. Using stable isotope analyses, we determined that allochthonous sources comprised 74% (±17%) of the food resources of aquatic invertebrates. However, the allochthonous contribution to aquatic invertebrates strongly decreased from shaded to open habitats, as light incidence increased in the tanks. The density of detritus in the tanks had no impact on the importance of allochthonous sources to aquatic invertebrates. This overall pattern held for all invertebrates, irrespective of the taxonomic or functional group to which they belonged. We concluded that, over a broad geographic range, aquatic food webs of tank bromeliads are mostly allochthonous‐based, but the relative importance of allochthonous subsidies decreases when light incidence favors autochthonous primary production. These results suggest that, for other freshwater systems, some of the between‐study variation in the importance of allochthonous subsidies may similarly be driven by the relative availability of autochthonous resources.